Cancer Patient Experience of Uncertainty While Waiting for Genome Sequencing Results - Bartley, Nicci; Napier, Christine E.; Butt, Zoe; Schlub, Timothy E.; Best, Megan C.; Biesecker, Barbara B.; Ballinger, Mandy L.; Butow, Phyllis (Frontiers in Psychology, 2021)
There is limited knowledge about cancer patients’ experiences of uncertainty while waiting for genome sequencing results, and whether prolonged uncertainty contributes to psychological factors in this context. To investigate uncertainty in patients with a cancer of likely hereditary origin while waiting for genome sequencing results, we collected questionnaire and interview data at baseline, and at three and 12 months follow up (prior to receiving results). Participants (N=353) had negative attitudes towards uncertainty (M=4.03, SD 0.68) at baseline, and low levels of uncertainty at three (M=8.23, SD 7.37) and 12 months (M=7.95, SD 7.64). Uncertainty about genome sequencing did not change significantly over time (t(210)=.660, p=.510). Greater perceived susceptibility for cancer (r(348)=.14, p<.01), fear of cancer recurrence (r(348)=.19, p<.01), perceived importance of genome sequencing ((r(350)=.24, p<.01), intention to change behavior if a gene variant indicating risk is found (r(349)=.29, p<.01), perceived ability to cope with results (r(349)=.36, p<.01), and satisfaction with decision to have genome sequencing (r(350)=.52, p<.01) were significantly correlated with negative attitudes towards uncertainty at baseline. Multiple primary cancer diagnoses (B=-2.364 [-4.238, -.491], p=.014), lower perceived ability to cope with results (B=-.1.881 [-3.403, -.359], p=.016) at baseline, greater anxiety about genome sequencing (avoidance) (B=.347 [.148, .546], p=.0012) at three months, and greater perceived uncertainty about genome sequencing (B=.494 [.267, .721] p=.000) at three months significantly predicted greater perceived uncertainty about genome sequencing at 12 months. Greater perceived uncertainty about genome sequencing at three months significantly predicted greater anxiety (avoidance) about genome sequencing at 12 months (B=.291 [.072, .509], p=.009). Semi-structured interviews revealed that while participants were motivated to pursue genome sequencing as a strategy to reduce their illness and risk uncertainty, genome sequencing generated additional practical, scientific and personal uncertainties. Some uncertainties were consistently discussed over the 12 months, while others emerged over time. Similarly, some uncertainty coping strategies were consistent over time, while other emerged while patients waited for their genome sequencing results. This study demonstrates the complexity of uncertainty generated by genome sequencing for cancer patients and provides further support for the inter-relationship between uncertainty and anxiety. Helping patients manage their uncertainty may ameliorate psychological morbidity.